Effects of Perceived Behavioral Control and Attitude on Knowledge Sharing among Engineers in Oil and Gas Companies - Mustafa Ahmed Hadi Almher; Banan Badeel Abdal (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
To enhance the job performance of engineers in the oil and gas sector, their knowledge and skills should be constantly updated through knowledge sharing. Perceived behavioural control and attitude have been identified as factors that contribute to effective knowledge sharing among employees. However, very little is known about perceived behavioural control and attitude toward knowledge sharing in the Iraqi oil and gas sector. Therefore, this study investigates the relationship between engineer’s perceived behavioural control and attitude on their intention towards knowledge sharing in public oil and gas firms in Iraq. To participate in the study, 240 engineers from oil and gas companies in Iraq were randomly selected. A questionnaire designed in a Likert scale format was used for the data collection. The data were analysed using descriptive statistical analysis and Correlation analysis. The results of the analysis show that there is a positive relation between engineer’s perceived behavioural control and attitude on their intention towards knowledge sharing in public oil and gas firms in Iraq. The study makes some recommendations on how to increase engineers’ perceived behavioural control and attitude and eventually increase their intention towards knowledge sharing.